2023
DOI: 10.1057/s41599-023-02206-8
|View full text |Cite
|
Sign up to set email alerts
|

Elementary school teachers’ attitudes towards project-based learning in China

Zhiling Cai,
Jinxing Zhu,
Yu Yu
et al.

Abstract: This study analyzed the Chinese elementary school teachers’ attitudes toward project-based learning (PBL) and identified factors that may influence elementary school teachers’ attitudes. The analysis was based on a questionnaire survey of 257 elementary school teachers and interviews with 10 elementary school teachers in China. Results showed that Chinese elementary school teachers generally had positive attitudes towards PBL, but their attitudes differed based on their educational level, years of teaching, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The findings align with previous research highlighting the transformative role of teachers in PjBL implementation (Cai et al, 2023). By adopting a facilitative role, teachers empower students to take ownership of their learning and develop essential 21st-century skills such as critical thinking, communication, and collaboration.…”
Section: Role As Facilitatorssupporting
confidence: 87%
See 2 more Smart Citations
“…The findings align with previous research highlighting the transformative role of teachers in PjBL implementation (Cai et al, 2023). By adopting a facilitative role, teachers empower students to take ownership of their learning and develop essential 21st-century skills such as critical thinking, communication, and collaboration.…”
Section: Role As Facilitatorssupporting
confidence: 87%
“…Scholars have emphasized the importance of authentic tasks, inquirybased learning, and collaboration in PjBL, highlighting its alignment with constructivist and sociocultural learning theories (do Amaral et al, 2023;Plews et al, 2024). Studies have shown that students engaged in PjBL projects demonstrate improved academic performance, higher motivation, and enhanced problem-solving skills than those in traditional classrooms (Abuhmaid et al, 2020;Cai et al, 2023;Zhang et al, 2024). Furthermore, research has identified various models and frameworks for designing and implementing PjBL, such as the Buck Institute for Education's (BIE) Gold Standard PBL model and the framework proposed by Thomas in Wijnia (Wijnia et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation